Students' Sustainable Waste Management Behaviors: Comparison Between Vocational and Public High School - Utami, Sagitaningtyas Susanti; Nuh, Mohammad; Sentanu, I Gede Eko Putra Sri (Dinamika Pendidikan, 2020)
This research aimed to comparing the behavior of high school students concerning sustainable waste management behavior between vocational and public school students. Management behaviors include waste prevention, reuse, recycling, green purchasing and waste disposal. The analysis uses a multivariate of covariance (MANCOVA) that the data collected by questionnaire involving 347 high school students in Tulungagung Regency. The findings presented here based on Protection Motivation Theory (PMT), from both types of schools it shows that threat appraisal has a significantly more influence on student’s participation in Sustainable Waste Management Behaviors (SWMBs) than Coping appraisal in the level of significance 5%. Furthermore, it is also revealed that there are significant differentiation (p0,05) SWMBs between the students of SMK 3 Boyolangu and SMA 1 Tulungagung. In order for students to understand the value of action and know which actions will mitigate waste effects, awareness must be provided to different forms of sustainable action strategies and the severity of waste disposal issues.